2018
DOI: 10.1021/acs.langmuir.8b01334
|View full text |Cite
|
Sign up to set email alerts
|

Stratification in Drying Films Containing Bidisperse Mixtures of Nanoparticles

Abstract: Large scale molecular dynamics simulations for bidisperse nanoparticle suspensions with an explicit solvent are used to investigate the effects of evaporation rates and volume fractions on the nanoparticle distribution during drying. Our results show that "small-on-top" stratification can occur when Pe ϕ ≳ c with c ∼ 1, where Pe is the Péclet number and ϕ is the volume fraction of the smaller particles. This threshold of Pe ϕ for "small-on-top" is larger by a factor of ∼α than the prediction of the model treat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 44 publications
(208 reference statements)
4
88
0
Order By: Relevance
“…We have previously shown that particles of different sizes have different thermophoretic responses to a thermal gradient. [30] In our previous work, only a thin layer of the liquid solvent adjacent to the bottom wall is thermalized at T l during evaporation, as shown in Fig. 1(a).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…We have previously shown that particles of different sizes have different thermophoretic responses to a thermal gradient. [30] In our previous work, only a thin layer of the liquid solvent adjacent to the bottom wall is thermalized at T l during evaporation, as shown in Fig. 1(a).…”
Section: Resultsmentioning
confidence: 95%
“…[30] In certain cases the "small-on-top" stratification expected by the existing theory [25] was even converted to "largeon-top" in the presence of strong evaporative cooling. [30] Based on the physical picture depicted above, it is natural to investigate the effects of a controlled thermal gradient on stratification in a drying suspension. In this paper, we explore this idea by comparing three types of thermalization schemes as sketched in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One can incorporate the hydrodynamic interactions by including the concentration-dependence in the diffusion constant. There are many recent studies on the effect of hydrodynamics on the non-equilibrium colloidal dynamics, mostly by evaporation [30][31][32][33][34][35] . One study on polymer solutions by Statt et al 32 showed that stratification happens in implicit solvent simulations, but not in explicit solvent simulations when hydrodynamic effects are included.…”
Section: Discussionmentioning
confidence: 99%